2019
DOI: 10.1055/s-0039-1695734
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Concomitant Treatments under Anticoagulants and Statins in Detecting Signals of Adverse Drug Reactions

Abstract: The aim of the present study was to evaluate the risk of adverse drug reactions (ADRs) of concomitant treatments in patients treated with anticoagulants and statins. The authors performed an observational cross-sectional study in two cohorts of surveyed patients treated with vitamin K antagonists (VKAs) or non–vitamin K antagonist oral anticoagulants (NOACs). Different groups were analyzed based on the drug that each patient was taking, that is, VKAs or NOACs, as well as on the use of HMG CoA reductase inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Reviewing the literature, only a few studies evaluated the risk of major bleeding in AF patients receiving statins and long-term anticoagulant therapy. Evidence shows that concurrent use of statins and VKA (warfarin) did not increase the risk of bleeding, but data with simultaneous DOACs and statins use was controversial ( 26 , 27 ). An earlier study reported a higher ICH risk in patients taking dabigatran and either simvastatin or lovastatin ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reviewing the literature, only a few studies evaluated the risk of major bleeding in AF patients receiving statins and long-term anticoagulant therapy. Evidence shows that concurrent use of statins and VKA (warfarin) did not increase the risk of bleeding, but data with simultaneous DOACs and statins use was controversial ( 26 , 27 ). An earlier study reported a higher ICH risk in patients taking dabigatran and either simvastatin or lovastatin ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study reported a higher ICH risk in patients taking dabigatran and either simvastatin or lovastatin ( 17 ). One observational study also suggested an increased bleeding risk with simultaneous use of DOACs and statins ( 27 ). On the other hand, a nationwide study from Taiwan found reduced major bleeding events with concurrent use of atorvastatin and DOACs ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, only the chemical subgroup C10AA "HMG CoA reductase inhibitors" [16] was considered in the analysis. This methodology approach has previously demonstrated robustness and consistency when all the ADR databases were applied to a specific group of drugs [17][18][19]. Details of the algorithm performed are reported (see Appendix 1).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, in patients who used both vitamin K antagonists and statins, the risk of ADR observed was lower than that of concomitant treatment with non-vitamin K antagonist oral anticoagulants and statins in an observational cross-sectional study. 26 Fourthly, a history of liver and biliary diseases should be checked before using statins. If the liver transaminase is elevated, differential diagnosis and treatment should be performed, and statins should be started after the transaminase has returned to normal.…”
Section: Liver Dysfunction Caused By Statinsmentioning
confidence: 99%